Coupling indoor airflow, HVAC, control and building envelope heat transfer in the Modelica Buildings library. Issue 4 (3rd July 2016) - Zuo, Wangda; Wetter, Michael; Tian, Wei; Li, Dan; Jin, Mingang; Chen, Qingyan
Abstract : This paper describes a coupled dynamic simulation of an indoor environment with heating, ventilation, and air conditioning (HVAC) systems, controls and building envelope heat transfer. The coupled simulation can be used for the design and control of ventilation systems with stratified air distributions. Those systems are commonly used to reduce building energy consumption while improving the indoor environment quality. The indoor environment was simulated using the fast fluid dynamics (FFD) simulation programme. The building fabric heat transfer, HVAC and control system were modelled using the Modelica Buildings library. After presenting the concept, the mathematical algorithm and the implementation of the coupled simulation were introduced. The coupled FFD–Modelica simulation was then evaluated using three examples of room ventilation with complex flow distributions with and without feedback control. Further research and development needs were also discussed.